Brad Bridgewater's Full Stroke at 165 m of His 200 m Backstroke Gold Medal Swim at the Atlanta Olympic Games 1996 - Rushall, B. S. (1999)
Video pictures (15 frames) and the appropriate technical/ biomechanical explanations for Brad Bridgewater's Full Stroke at 165 m of His 200 m Backstroke Gold Medal Swim at the Atlanta Olympic Games 1996.